Implementation Of A Ray Tracing Simulator For Propagation Prediction - Thirumaraiselvan, P. (2006)
In wireless communication, understanding of the propagation channels is necessary to achieve optimum performance of a communication system. Even though direct measurements enable accurate evaluation of onsite performance, it requires a considerable amount of time and efforts. Therefore, a computer tool that could characterize the wireless channel from the building plans and material properties would be a good solution. This project considers an approach for developing such a simulation tool using ray tracing.